2013
DOI: 10.1517/17460441.2013.815163
|View full text |Cite
|
Sign up to set email alerts
|

The preclinical profile of lurasidone: clinical relevance for the treatment of schizophrenia

Abstract: Lurasidone demonstrated high affinity for serotonin 5-HT(1A), 5-HT(2A), 5-HT₇, dopamine D₂ and adrenergic α(2C) receptors followed by α₁ and α(2A) receptors. The drug was active in animal models predictive of antipsychotic and antidepressant activities. In addition, it demonstrated procognitive effects, as it was effective in several animal models that assessed memory, cognition and executive functions in rats and in primates. At a cellular level, lurasidone promotes neuronal plasticity, can modulate epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 78 publications
2
18
0
Order By: Relevance
“…Our results suggest that, in addition to synaptic and neuroplastic mechanisms (Tarazi and Riva, 2013; Luoni et al, 2014), lurasidone is able to modulate the brain oxidative balance, which may contribute to its therapeutic effects and eventually enhance neuronal resiliency. Interestingly, similar mechanisms have also been described for other psychotropic drugs, including antidepressants (Martín-Hernández et al, 2016; Omar and Tash, 2017) and antipsychotics (MacDowell et al, 2016).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our results suggest that, in addition to synaptic and neuroplastic mechanisms (Tarazi and Riva, 2013; Luoni et al, 2014), lurasidone is able to modulate the brain oxidative balance, which may contribute to its therapeutic effects and eventually enhance neuronal resiliency. Interestingly, similar mechanisms have also been described for other psychotropic drugs, including antidepressants (Martín-Hernández et al, 2016; Omar and Tash, 2017) and antipsychotics (MacDowell et al, 2016).…”
Section: Discussionmentioning
confidence: 80%
“…We also investigated the effect of a chronic treatment with lurasidone in counteracting the CMS-induced alterations in rat hippocampus. Lurasidone is a multi-receptor antipsychotic drug (Tarazi and Riva, 2013) with demonstrated clinical efficacy for cognitive deficits in schizophrenia (Harvey et al, 2013) and in bipolar disorder (Yatham et al, 2017) and depressive symptoms in schizophrenia (Nasrallah et al, 2015) and in bipolar depression (Loebel et al, 2014). We previously demonstrated that chronic lurasidone is able to normalize the stress-induced depressive-like behaviors as well as the neuroplastic and inflammatory alterations observed in stressed rats (Luoni et al, 2014; Rossetti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an overall dampening of stress-induced neuroinflammation was observed following chronic treatment with the tricyclic antidepressant imipramine, with the novel antidepressant agomelatine that acts as MT1/MT2 melatonergic agonist and 5HT 2C antagonist [52], as well as with the multi-receptor antipsychotic drug lurasidone, which has high affinity for dopamine D2 receptors as well as for 5-HT1A, 5-HT2A and 5-HT7 serotonin receptors [32]. These results suggest that the ability of these drugs to modulate CMS-induced inflammatory changes appears to be independent from their primary effect at synaptic level, but may be due to shared long-term adaptive mechanisms induced by their repeated administration.…”
Section: Discussionmentioning
confidence: 99%
“…of vehicle (hydrossi-ethil-cellulose, HEC 1%), imipramine (10 mg/kg daily) or agomelatine (40 mg/kg daily) with a dosage chosen according with previous data [30]. Another group of animals received oral administration (by gavage) of vehicle (HEC 1%) or lurasidone (3 mg/kg daily); this dose and route of delivery were chosen based on previous studies [31,32]. The stress was continued throughout the entire period of drugs administration.…”
Section: Stress Procedures and Pharmacological Treatmentmentioning
confidence: 99%
“…In the hippocampus, the effect is caused by the increased extracellular levels of some neurotransmitters such as glutamate through metabotropic receptors [54]. Thus, the effects of lurasidone on cognition and behavioral improvement are due to the acute effect of dosages in the hippocampus [12] related to improved synaptic plasticity with structural remodeling and functional changes [55]. They are likely to be determined in conjunction with other synergistic effects with the key role of low-dosage blockade of 5-HT 7 receptors that improves cognition [56] and increases mood [57].…”
Section: Development Of Clinical Studies On Lurasidonementioning
confidence: 99%